2012
DOI: 10.1145/2366145.2366193
|View full text |Cite
|
Sign up to set email alerts
|

Gaze correction for home video conferencing

Abstract: Figure 1: Top: frames recorded during video-conferencing. Note the lack of eye contact because of the disparity between the locations of the participant and the camera. Bottom: real-time gaze correction with the proposed algorithm. AbstractEffective communication using current video conferencing systems is severely hindered by the lack of eye contact caused by the disparity between the locations of the subject and the camera. While this problem has been partially solved for high-end expensive video conferencin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(63 citation statements)
references
References 27 publications
0
63
0
Order By: Relevance
“…From these results, we confirmed that our method works properly in real environments since the differences in the extrinsic parameters estimated by each method are small. While this precision is not enough for eye gaze tracking, it is acceptable for applications that do not need high precision, such as gaze correction [12] using a display and attached web camera system.…”
Section: Real Data 421 Configurationmentioning
confidence: 99%
See 1 more Smart Citation
“…From these results, we confirmed that our method works properly in real environments since the differences in the extrinsic parameters estimated by each method are small. While this precision is not enough for eye gaze tracking, it is acceptable for applications that do not need high precision, such as gaze correction [12] using a display and attached web camera system.…”
Section: Real Data 421 Configurationmentioning
confidence: 99%
“…They assume that the user's gaze points represent his/her interests in the contents on display. As another example, Kuster et al [12] propose a gaze correction method with a display-camera setup for home video conferences. For these applications, they have to know the relative posture and position of the camera against the display.…”
Section: Introductionmentioning
confidence: 99%
“…The absence of direct eye contact in video conferencing is critical to investigate natural social interactions, for which mutual gaze is a central element eliciting a sense of presence and an engagement (Senju & Johnson, 2009). Recently, technical solutions to this limitation have been proposed, based on online video correction (Kuster et al, 2012). An alternative option is the use of a device based on a semi-transparent mirror system.…”
Section: Further Developmentsmentioning
confidence: 99%
“…More recently this approach has been extended with the use of depth sensors for better results, such as in [12]. Very visually promising results are also presented in [4] where a Kinect is used to rotate a facial texture in a video frame making it appear as if the person is looking straight at the camera. Notably [5] demonstrates the capturing of an entire environment into a 3D model, and subsequent rendering of virtual viewpoints in real time.…”
Section: Related Workmentioning
confidence: 99%